Calcifying epithelial odontogenic cyst of the mandible - Nigel R Figueiredo; Manoj Meena; Ajit D Dinkar; Manisha Khorate (Wolters Kluwer Medknow Publications, 2014)
The calcifying epithelial odontogenic cyst (CEOC) is a developmental odontogenic cyst, which was first categorized as a distinct entity by Gorlin in 1962. It is an unusual and unique lesion, which may show characteristics of both a solid neoplasm and a cyst. It usually occurs as an intra-osseous lesion but may occasionally occur as an extra-osseous or peripheral variant. It shows a nearly equal distribution between the maxilla and mandible and is commonly seen anterior to the first molar. The clinical and radiographic features of this lesion are not pathognomonic, and it is characterized by its histological diversity, with the most characteristic feature being the presence of a variable number of ghost cells within the epithelial component. Treatment is conservative with surgical enucleation, and recurrences are rare. This report describes a case of CEOC in association with an impacted mandibular first premolar, which was diagnosed in a 13-year-old female patient, along with a review of the literature.